(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Turnover is characterized by turnover intention which can be influenced by work involvement, financial compensation, and non-physical work environment. The purpose of this study was to determine the effect of work involvement, financial compensation, and non-physical work environment on turnover intention. This research was conducted at AQ VA Hotel & Villas in Legian, Bali on all 31 employees using the census technique. Data was collected using interviews, observation, documentation, and questionnaires which were measured using a five-choice Likert scale. The instrument test was carried out with validity and reliability tests. The data analysis technique used multiple linear regression analysis, determination test, model feasibility test, and partial significance test. The results of the analysis prove that work involvement, financial compensation, and non-physical work environment have a significant negative effect on turnover intention.